Chinese Temples and Buddhism Unite In Harmony - Ardian Cangianto (STAB Kertarajasa, 2022)
Relationship history between China and Indonesia Archipelago has been recorded since 1st century and followed by Chinese community to migrate to the archipelago at that time. The migration also brought their beliefs and culture to enrich archipelago culture. Chinese people and their temples role in developing Buddhism were not discussed in detail, even, there were many misunderstandings between temples and Buddhism institutions. Further, to overcome this problem, we must understand how Chinese belief system and temple role in developing Buddhism in 18th to 21st centuries. Chinese temple's track record is dominant in Buddhism development. Benqing monk's record who traveled from one temple to another in providing services for people in temples or Mahayana Buddhist was possible to be traced. In addition, role of Dizang Yuan in Jakarta to educate the